PROBLEMS OF GENERAL PRACTITIONER-PATIENT COMMUNICATION IN BULGARIA - Biserka I. Vasileva; Milena D. Karcheva (Peytchinski Publishing, 2023)
Effective doctor-patient communication is considered an important prerequisite in providing high-quality medical care. In modern healthcare, a new model of patient-centered collaboration and partnership is established. A general practitioner's communication culture and skills are crucial parts of his/her qualification and activities and have a direct influence on the doctor-patient relationship and form a patient's trust in the GP. Our study aimed to analyze the problems arising in the process of doctor-patient communication. Material/Methods: An anonymous inquiry with a questionnaire was conducted between September, 1 and September 30, 2018, in the Pleven region, Bulgaria with 1053 respondents visiting their GPs during this period. The data we collected through empirical research is presented and evaluated, based on a general analysis of the communication act. The results obtained were processed with Microsoft Office Excel 2007. The quantitative analysis was performed with SPSS 17.0. Results: The analysis elucidated weaknesses and unsolved problems in doctor-patient communication. A particularly serious problem identified was that of verbal communication of the physicians with their patients: the ability to ask questions and listen, explain, and guide patients on proper behavior and lifestyle. Conclusions: There are problems concerning doctor-patient communication. Verbal communication is a major problem, which could be attributed to insufficient training. We recommend improving and updating the communicative skills training programs for physicians and other health care professionals in primary care.